Reliable kidney size determination by magnetic resonance imaging in pathophysiological settings. (22nd June 2021) - Gladytz, Thomas; Millward, Jason M.; Cantow, Kathleen; Hummel, Luis; Zhao, Kaixuan; Flemming, Bert; Periquito, Joāo S.; Pohlmann, Andreas; Waiczies, Sonia; Seeliger, Erdmann; Niendorf, Thoralf
Abstract: Aim: Kidney diseases constitute a major health challenge, which requires noninvasive imaging to complement conventional approaches to diagnosis and monitoring. Several renal pathologies are associated with changes in kidney size, offering an opportunity for magnetic resonance imaging (MRI) biomarkers of disease. This work uses dynamic MRI and an automated bean‐shaped model (ABSM) for longitudinal quantification of pathophysiologically relevant changes in kidney size. Methods: A geometry‐based ABSM was developed for kidney size measurements in rats using parametric MRI (T2, T2 * mapping). The ABSM approach was applied to longitudinal renal size quantification using occlusion of the (a) suprarenal aorta or (b) the renal vein, (c) increase in renal pelvis and intratubular pressure and (d) injection of an X‐ray contrast medium into the thoracic aorta to induce pathophysiologically relevant changes in kidney size. Results: The ABSM yielded renal size measurements with accuracy and precision equivalent to the manual segmentation, with >70‐fold time savings. The automated method could detect a ~7% reduction (aortic occlusion) and a ~5%, a ~2% and a ~6% increase in kidney size (venous occlusion, pelvis and intratubular pressure increase and injection of X‐ray contrast medium, respectively). These measurements were not affected by reduced image quality following administration of ferumoxytol. Conclusion: Dynamic MRI in conjunction with renal segmentation using an ABSM supports longitudinal quantification of changes in kidney size in pathophysiologically relevant experimental setups mimicking realistic clinical scenarios. This can potentially be instrumental for developing MRI‐based diagnostic tools for various kidney disorders and for gaining new insight into mechanisms of renal pathophysiology.